2019
DOI: 10.1021/acscatal.9b05224
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Induced Restructuring of Pd@CeO2 and Pd@SiO2 Nanoparticles as a Strategy for Enhancing Low-Temperature Catalytic Activity

Abstract: Retaining high catalytic activity after exposure to elevated temperatures remains a crucial challenge for applications such as automotive emissions control. While catalysts generally sinter and lose activity after aging at high temperature, here we illustrate that palladium in a core@shell morphology responds very differently. After 800 °C aging in oxygen, palladium redisperses into the encapsulating shell. The redispersion is more pronounced, and nearly complete, when palladium is encapsulated by reducible ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 72 publications
2
45
0
Order By: Relevance
“…Carrillo et al [38] reported that PdO nanoparticles can trap mobile Pt species under oxidizing conditions, which is of high relevance for understanding the behavior of bimetallic Pt-Pd catalysts. Lately, a wide variety of advanced materials has been proposed for catalytic emission control under lean conditions, namely encapsulated coreshell catalysts [25,39,40] and nanostructured architectures [41,42] for oxidation reactions and microporous materials for NOx control [43][44][45][46]. Although these materials often show extremely promising catalytic activity or stability, fundamental in-depth understanding, transfer into industrial application and upscaling of preparation procedures remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Carrillo et al [38] reported that PdO nanoparticles can trap mobile Pt species under oxidizing conditions, which is of high relevance for understanding the behavior of bimetallic Pt-Pd catalysts. Lately, a wide variety of advanced materials has been proposed for catalytic emission control under lean conditions, namely encapsulated coreshell catalysts [25,39,40] and nanostructured architectures [41,42] for oxidation reactions and microporous materials for NOx control [43][44][45][46]. Although these materials often show extremely promising catalytic activity or stability, fundamental in-depth understanding, transfer into industrial application and upscaling of preparation procedures remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…The three model catalyst systems prior to cycled aging (referred to as initial catalysts) are shown in the first column of Figure 1. We note that these catalysts were prepared following previously described methods 15,16,25 and have been exposed to 500°C in air for 2 hours (see Methods Section for more information). The Pd@SiO2 and Pd@CeO2 have comparable Pd core size on the order of 3 -5 nm in diameter and similar oxide shell thickness of approximately 10 -12 nm.…”
Section: Defining Model Catalyst Systemsmentioning
confidence: 99%
“…13,14 We have recently shown that such core@shell architectures can facilitate favorable and counter-intuitive restructuring when exposed to the high-temperature (800°C) conditions common to many catalytic applications. 15,16 Specifically, we discovered that core Pd disintegrated and migrated outward into the encapsulating shell, nearly doubling the number of available sites for reaction. The resulting highly dispersed Pd species formed an arrangement that resembled a "halo" around the original location of the core.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its low cost and excellent CO oxidation performance when combined with CeO 2 , Pd has attracted extensive attention. [ 66–69 ] As mentioned earlier, in the low‐temperature catalytic reaction, small metal particle size usually shows good catalytic activity; [ 70,71 ] Pd can be evenly dispersed on the surface of the support and exhibit high catalytic activity. [ 56,72,73 ] The catalytic reaction is usually conducted at a high temperature, which results in the sintering of small metal NPs and the reduction of catalyst active sites.…”
Section: Loading Metals Onto Ceo2mentioning
confidence: 99%